2022
DOI: 10.1088/1367-2630/ac788f
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of dynamical control of three-level open systems with a superconducting qutrit

Abstract: We propose a method for the dynamical control in three-level open systems and realize it in the experiment with a superconducting qutrit. Our work demonstrates that in the Markovian environment for a relatively long time (3 $\mu$s), the systemic populations or coherence can still strictly follow the preset evolution paths. This is the first experiment for precisely controlling the Markovian dynamics of three-level open systems, providing a solid foundation for the future realization of dynamical control in mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…One may consider the quantum dynamics of the present system by the quantum state diffusion method. [31,53,54] Besides, one may use various protocols to accelerate the dynamics approaching chaos, such as shortcut to adiabaticity [55][56][57][58][59][60][61][62][63] or Lyapunov control. [64,65] It has been demonstrated that this procedure is effective about the study of chaos in the optomechanical system.…”
Section: Discussionmentioning
confidence: 99%
“…One may consider the quantum dynamics of the present system by the quantum state diffusion method. [31,53,54] Besides, one may use various protocols to accelerate the dynamics approaching chaos, such as shortcut to adiabaticity [55][56][57][58][59][60][61][62][63] or Lyapunov control. [64,65] It has been demonstrated that this procedure is effective about the study of chaos in the optomechanical system.…”
Section: Discussionmentioning
confidence: 99%
“…As now, a variety of theoretical efforts have been made, including examining how quantum resources affect QB performance [10][11][12][13], presenting models for achieving optimal mechanisms for batteries such as high charging and capacity [14][15][16][17][18], slow erosion [19,20], to discussing the environmental effects on charg-ing and discharging of QBs [21][22][23][24][25][26][27]. Furthermore, several experimental platforms have been studied to realize operational quantum batteries [28][29][30][31][32][33]. In this regard, we can address the use of an organic semiconductor that is composed of two-levels systems connected to a microcavity [28].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, QBs can be represented by semiconductor quantum dots embedded within optical microcavities, where energy is exchanged between the solid-state qubit and light fields during charging and discharging [29]. Superconducting circuits are also another field of experimental research for quantum batteries [30,31]. An example is the transmon qutrit QB, which is composed of a three-level transmon coupled to an external field.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its significant application in QEC, parity measurement also plays an important role in the field of quantum information processing (QIP), [13][14][15][16][17][18][19][20][21][22][23][24] such as quantum computation, [25][26][27][28][29][30][31] generating entangled states, [32][33][34][35][36][37][38][39][40] purifying entangled states, [41][42][43][44][45][46] and quantum teleportation. [47][48][49] Traditional parity measurement destroys the original state in the system while obtaining parity information, which leads to the waste of quantum entanglement resources.…”
Section: Introductionmentioning
confidence: 99%